Assessment of Disaster Loss Index and Characteristics of Gale Disaster in Typical Arid and Semiarid Lands - Baoxin Chen; Xu Wang; Xi Wang; Shengqing Zhou; Hanxiang Gong (Discrete Dynamics in Nature and Society)
This study aims to illustrate the various characteristics of gale disaster loss in typical arid and semiarid areas and to divide the classification of disaster loss. Based on 1399 gale disasters in 48 counties (or cities) of Southern Xinjiang, the typical arid and semiarid lands, during 1980–2019, the disaster loss index, which comprehensively expresses six disaster factors, is constructed through mathematical statistics. The percentile method is used to divide the disaster loss index into four levels: mild (level I), moderate (level II), severe (level III), and very severe (level IV). The geographical distribution, annual variation, and interannual variation characteristics of the frequency and intensity of gale disasters in Southern Xinjiang were analyzed from the overall and different levels. The results show that the most frequent and hardest-hit areas in Southern Xinjiang are concentrated in Turpan and Aksu. The gale disasters have their peak occurrence in April with the most vigorous intensity. The frequency of gale disasters in Southern Xinjiang has increased yearly, but the intensity did not show a fluctuation trend. The frequency and intensity of level I to III gale disasters increased yearly, but the frequency and intensity of level IV gale disasters did not fluctuate. Identifying high-risk areas and periods of gale disaster loss is conducive to the policy formulation and hierarchical management of disaster prevention and control in arid and semiarid lands.